ENCUESTA DE CALIDAD DE VIDA 2009 - -CEO-, Centro de Estudios de Opinión; Castaño, Elkin (La Sociología en sus Escenarios, 2010)
Abstract. 2001, the Department of Metropolitan Planning of the city of Medellín realised the Survey of Quality of Vida (ECV), which collected excellent on the conditions of life of the inhabitants of the city. In the 2002, Brown ET to., constructed to an urban indicator and one rural one to measure the conditions of life in the city being had as it bases the information provided by this survey. These indicators allowed to obtain measurements on the conditions of life for the homes in each commune of the urban area, and each group of judges of the rural area. As of year 2004, Metropolitan Planning has continued realising the ECV annually with the purpose of to investigate the evolution of the conditions of life of the homes of the city with respect to the found ones in the basic information of year 2001. The objective of this document is to present/display the update of the measurements of conditions of life in the communes and groups of judges of the city based on the Survey of Quality of Life for year 2009 and for presenting/displaying its evolution from the 2001. This update consists of applying the new elaborated information to the ICV with the ECV of the 2001. Resumen. En el año 2001, el Departamento de Planeación Metropolitana de la ciudad de Medellín realizó La Encuesta de Calidad de Vida (ECV), la cual recogió información relevante sobre las condiciones de vida de los habitantes de la ciudad. En el 2002, Castaño et al., construyeron un indicador urbano y uno rural para medir las condiciones de vida en la ciudad teniendo como base la información proporcionada por dicha encuesta. Estos indicadores permitieron obtener mediciones sobre las condiciones de vida para los hogares en cada comuna del área urbana, y cada corregimiento del área rural. A partir del año 2004, Planeación Metropolitana ha seguido realizando anualmente la ECV con el fin de investigar la evolución de las condiciones de vida de los hogares de la ciudad con respecto a las halladas en la información de base del año 2001. El objetivo de este documento es presentar la actualización de las mediciones de condiciones de vida en las comunas y corregimientos de la ciudad basada en la Encuesta de Calidad de Vida para el año 2009 y presentar su evolución desde el 2001. Esta actualización consiste en aplicar la nueva información al ICV elaborado con la ECV del 2001.